2000
DOI: 10.1002/1096-8628(20000703)93:1<58::aid-ajmg10>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Are hereditary hemochromatosis mutations involved in Alzheimer disease?

Abstract: Mutations in the class I-like major histocompatibility complex gene called HFE are associated with hereditary hemochromatosis (HHC), a disorder of excessive iron uptake. We screened DNA samples from patients with familial Alzheimer disease (FAD) (n = 26), adults with Down syndrome (DS) (n = 50), and older (n = 41) and younger (n = 52) healthy normal individuals, for two HHC point mutations-C282Y and H63D. Because the apolipoprotein E (ApoE) E4 allele is a risk factor for AD and possibly also for dementia of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 71 publications
5
66
0
Order By: Relevance
“…A significant reduction in transferrin levels is observed in PD and AD and has been suggested as a contributory factor to increases in iron concentrations due to the resulting iron dysregulation [111]. Genetic mutations that impact iron homeostatic mechanisms are associated with certain neurodegenerative disorders [112,113] and may offer an explanation for abnormal iron metabolism in some neurodegenerative disorders. Another theory proposes the possibility of peripheral iron entry into the brain through a disrupted BBB [24].…”
Section: Iron and Neurodegenerationmentioning
confidence: 99%
“…A significant reduction in transferrin levels is observed in PD and AD and has been suggested as a contributory factor to increases in iron concentrations due to the resulting iron dysregulation [111]. Genetic mutations that impact iron homeostatic mechanisms are associated with certain neurodegenerative disorders [112,113] and may offer an explanation for abnormal iron metabolism in some neurodegenerative disorders. Another theory proposes the possibility of peripheral iron entry into the brain through a disrupted BBB [24].…”
Section: Iron and Neurodegenerationmentioning
confidence: 99%
“…We also observed that gene variants involved in iron metabolism (hemochromatosis H63D (HFE H63D) and transferrin C2 (TfC2) variants) are associated with higher brain iron levels in healthy older men (Bartzokis et al, 2010). These two gene variants are highly prevalent (affecting approximately 50% of the population), and some studies have shown an association of these variants with higher risk of developing AD (Connor and Lee, 2006;Lehmann et al, 2010;Sampietro et al, 2001;Moalem et al, 2000). We therefore examined memory function in the context of gender and the presence (IRON + ) or absence (IRONÀ) of these iron gene variants.…”
Section: Introductionmentioning
confidence: 75%
“…33 In another study, in patients with familial AD (FAD) C282Y and H63D mutations were over-represented in men and under-represented in women with FAD. 34 Thus, the possibility that HFE mutations are important new genetic risk factors for AD should be pursued further.…”
Section: Discussionmentioning
confidence: 99%